DEVELOPMENT OF THE NATIONAL MOVEMENT OF THE CRIMEAN TATAR (LATE XX– EARLY XXI CENTURIES) - Бекіров, С.Н. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
In the article the features of development of national motion of Crimean Tatars are analysed after returning to Crimea. The thesis deals with various historical and political grounds and conditions for the rise of the Crimean Tatars national movement. In the present research its main stages of development, political ideas, peculiarities, forms and methods of its activities, its differentiation processes and interaction with political forces of Crimea and Ukraine are characterized; main possible variants of the Crimean Tatars national movement further development on the contemporary stage are modeled.